Effects of defects on the electronic and optical properties of TiO2 nanosheet. (14th October 2019) - Jin, Fan; Zhang, Xiao; Wei, Min; Ma, Yuchen
Abstract: Due to the unique properties of 2D materials, TiO2 nanosheet has been widely studied for applications in photocatalysis and electrochemical energy storage. Just as its counterpart of the 3D TiO2 crystal, defects are also expected to play an important role in the properties of TiO2 nanosheet. In this work, by the GW method and Bethe–Salpeter equation (BSE) we systematically investigate the excited-state properties of the lepidocrocite-type TiO2 (L-TiO2 ) nanosheet. Our results show that the computed electronic band gap and the ultraviolet (UV) absorption edge of the perfect nanosheet deviate from the experiment greatly. When there exist Ti vacancies, the electronic band gap of L-TiO2 is narrowed by 1.1 eV, making the calculation match the experiment. Ti vacancies reduce the exciton binding energy of L-TiO2 from 1 eV to 0.1 eV, which decreases recombination probability of the photogenerated electron and hole and is beneficial for photocatalysis. Other defects, such as oxygen vacancies, do not have pronounced effect on the electronic and optical properties of L-TiO2 . We find that density functional theory (DFT) with the Hubbard U correction fails to predict the important band-gap narrowing phenomenon of L-TiO2 .